The Role of Program Diversification in Shaping Student Enrollment Decisions in Higher Education - Fauzi, Rizki; Fathurrahman, Hanif Zirly; Rahmawati, Linda; Fauziyah, Azizah; Nandang, Nandang (Journal Corner of Education, Linguistics, and Literature, 2024)
In the current era, technological advancements significantly influence consumer attitudes and behaviors regarding the selection, consumption, and utilization of products perceived to possess high quality and standards. The purchasing decision is an integral aspect of consumer behavior, encompassing the study of how individuals, groups, and organizations choose, buy, and use goods, services, ideas, or experiences to fulfill their needs and desires. This research aims to examine the impact of product diversification (X) on purchasing decisions (Y) within the Meatrix business located in Pandeglang, Banten. The findings and discussions of this study lead to a general conclusion regarding the concept of product diversification, which is categorized as good based on consumer ratings. This indicates that the highest indicator within the product diversification variable is consumer needs and expectations, while the lowest indicator pertains to ready-to-consume products. Furthermore, the purchasing decision variable is also categorized as good, with the highest indicator being product selection and the lowest indicator related to the choice of distribution channels.